A Functional Approach towards Understanding the Role of the Mitochondrial Respiratory Chain in an Endomycorrhizal Symbiosis - Mercy, Louis; Lucic-Mercy, Eva; Nogales, Amaia; Poghosyan, Areg; Schneider, Carolin; Arnholdt-Schmitt, Birgit (Frontiers in Plant Science, 2017)
Arbuscular mycorrhizal fungi (AMF) are crucial components of fertile soils, able to provide several ecosystem services for crop production. Current economic, social and legislative contexts should drive the so-called “second green revolution” by better exploiting these beneficial microorganisms. Many challenges still need to be overcome to better understand the mycorrhizal symbiosis, among which (i) the biotrophic nature of AMF, constraining their production, while (ii) phosphate acts as a limiting factor for the optimal mycorrhizal inoculum application and effectiveness. Organism fitness and adaptation to the changing environment can be driven by the modulation of mitochondrial respiratory chain, strongly connected to the phosphorus processing. Nevertheless, the role of the respiratory function in mycorrhiza remains largely unexplored. We hypothesized that the two mitochondrial respiratory chain components, alternative oxidase (AOX) and cytochrome oxidase (COX), are involved in specific mycorrhizal behavior. For this, a complex approach was developed. At the pre-symbiotic phase (axenic conditions), we studied phenotypic responses of Rhizoglomus irregulare spores with two AOX and COX inhibitors [respectively, salicylhydroxamic acid (SHAM) and potassium cyanide (KCN)] and two growth regulators (abscisic acid – ABA and gibberellic acid – Ga3). At the symbiotic phase, we analyzed phenotypic and transcriptomic (genes involved in respiration, transport, and fermentation) responses in Solanum tuberosum/Rhizoglomus irregulare biosystem (glasshouse conditions): we monitored the effects driven by ABA, and explored the modulations induced by SHAM and KCN under five phosphorus concentrations. KCN and SHAM inhibited in vitro spore germination while ABA and Ga3 induced differential spore germination and hyphal patterns. ABA promoted mycorrhizal colonization, strong arbuscule intensity and positive mycorrhizal growth dependency (MGD). In ABA treated plants, R. irregulare induced down-regulation of StAOX gene isoforms and up-regulation of genes involved in plant COX pathway. In all phosphorus (P) concentrations, blocking AOX or COX induced opposite mycorrhizal patterns in planta: KCN induced higher Arum-type arbuscule density, positive MGD but lower root colonization compared to SHAM, which favored Paris-type formation and negative MGD. Following our results and current state-of-the-art knowledge, we discuss metabolic functions linked to respiration that may occur within mycorrhizal behavior. We highlight potential connections between AOX pathways and fermentation, and we propose new research and mycorrhizal application perspectives.